The role of control and self-efficacy in predicting student's academic motivation - . .; . .; . .; . . (پژوهش در نظام‌های آموزشی, 2016)
The purpose of this study was to determine the relationship between control and self-efficacy with academic motivation in students. The statistical population of the study consisted of all students of state-of-the-art undergraduate and graduate high school students who studied in Tehran during the academic year of 93-92. A multistage cluster sampling method was used to select the sample. According to the research plan, 200 people were selected and responded to the scale of academic motivation (Valerand et al., 1989), internalism, powerful people and luck (Levinson, 1981) and generalized self-efficacy questionnaire (Jayge et al., 1998). The results of regression analysis showed that the two variables of control and self-efficacy were able to explain 13% of internal motivation variance, 7% of external stimulation variance and 9% of non-motivational variance. Finally, the findings were discussed based on the importance of academic motivation in students' academic achievement.